Antecedents and Consequences of Motivational: How Leadership, Organizational Culture and Competence Affect Performance (Jurnal Manajemen Bisnis, 2021)
The study collected primary data from 131 respondents via questionnaires and used the entire population as a sample. The study lasted three months, from April to June 2021. Structural Equation Modeling (SEM) was used to analyze the data. The findings of this study indicate that: (1) motivation is positively influenced by leadership, organizational culture, and competence. (2) While leadership has a positive but not statistically significant effect on performance, organizational culture, competence, and motivation all have a positive and statistically significant impact on performance. (3) While leadership and competence have a positive and significant effect on motivational performance, organizational culture has a positive but insignificant effect on motivational performance. This means that while leadership and competence have been shown to increase the motivation of the State Civil Apparatus, leadership alone has not been shown to increase performance, while good organizational culture, competence, and motivation have been shown to increase performance. On the other hand, leadership and competence have been shown to increase performance through motivation, whereas organizational culture, competence, and motivation have been shown to increase performance.